169 The Effect of Increasing Valine, Isoleucine, and Tryptophan:Lysine Ratios on Growth Performance and Carcass Characteristics of Pigs Fed Diets with High Leucine:Lysine. (12th April 2022) - Williams, Hadley; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Gebhardt, Jordan T; Hastad, Chad W; Post, Zach; Haydon, Keith D
Abstract: A total of 4, 076 pigs (initially 39.3 kg) were used across 2 experiments to evaluate the effect of increasing ratios of Val, Ile, and Trp:Lys in corn-soybean meal-DDGS-based diets on pig growth performance and carcass characteristics. In both experiments, the 4 dietary treatments were: 1) high soybean meal and low feed grade amino acids (control), 2) low soybean meal and high feed grade amino acids, with Val:Lys, Ile:Lys, and Trp:Lys at 67, 55, and 18, respectively, (low ratio) 3) diet 2 except Val:Lys, Ile:Lys, and Trp:Lys increased to 72, 60, and 21, respectively, (medium ratio), and 4) diet 2 except Val:Lys, Ile:Lys, and Trp:Lys at 80, 65, and 23, respectively (high ratio). The Leu:lys levels for the diets with increased synthetic amino acids ranged from 135 to 146 for the 4 phases. All diets contained 30% DDGS until 100 kg BW, and then 20% DDGS until trial completion. Because there was no experiment × treatment interactions, data from both experiments were combined. Overall, ADG and ADFI increased (AA ratio; linear, P < 0.05) as Val, Ile, and Trp:Lys ratios increased from low to high. Pigs fed the control diet exhibited increased ADG compared with pigs fed low ratio diets, while pigs fed medium and high ratio diets performed intermediate. For carcass characteristics, pigs fed the control had increased ( P < 0.05) percentage lean and loin depth compared with pigs fed the medium ratio diet, with pigs fed low and high ratio intermediate. Pigs fed the medium ratio diet had increased backfat depth compared with pigs fed the control, with pigs fed the low and high ratio intermediate ( P < 0.05). In summary, the soybean meal level can be reduced, and synthetic amino acid levels increased in high DDGS diets as long as ratios of Val, Ile, and Trp to Lys are increased.